Analisis Faktor-Faktor yang Berhubungan dengan Pelaksanaan Discharge Planning di Instalasi Rawat Inap Bedah Rsud Dr. Iskak Tulungagung - Eva Nur Aini; Andika Siswoariwibowo; Yuli Nurhayati (STIKES Karya Husada Kediri, 2018)
There are five factors which effect on the implementation of discharge planning. They are; discharge planning personnel, participation in discharge planning, communication in discharge planning, time, and discharge planning agreement. This study aimed to analyze the factors that affect the Implementation of Discharge Planning on nurse in Surgical IRNA RSUD dr. Iskak. The design used in this study was descriptive explorative. The research variable was factor which affects the implementation of discharge planning on nurse in Surgical IRNA RSUD dr. Iskak, with the population of 35 nurses. The sampling technique was purposive sampling technique using multiple linear regression formula. The results showed that only discharge planning personnel and the participation of discharge planning have an influence. And the most influenced factor of discharge planning was personnel factor with statistical test results obtained Sig ( ) = 0.007 < 0.05 (α) and the value of R Square Linear was 0.933. The results showed that personnel factor was the most influenced, because it was supported by age, work duration, and last education. So the personnel influenced high on discharge planning. Based on the results of the study, it can be concluded that the most influenced factor is the personnel factor to discharge planning on nurse in Surgical IRNA RSUD dr. Iskak. It is advisable to develop knowledge about the factors that influence discharge planning.